2015
DOI: 10.3109/09540261.2015.1049128
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perspectives on care of children with autistic spectrum disorder in South Asia – Views from Pakistan and India

Abstract: Autism spectrum disorder (ASD) affects about 1.4% of the population in South Asia but very few have access to any form of health care service. The objective of this study was to explore the beliefs and practices related to the care of children with ASD to inform strategies for intervention. In Pakistan, primary data were collected through in-depth interviews of parents (N = 15), while in India a narrative review of existing studies was conducted. The results show that the burden of care is almost entirely on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 33 publications
8
113
0
3
Order By: Relevance
“…Our research supports the findings of other recent studies in Australia (Broady, Stoyles, and Morse 2015), Nepal (Heys et al 2016), Pakistan and India (Minhas et al 2015), China (Lu et al 2015), the USA and Canada (Kinnear et al 2016) that suggest stigma continues to be a significant challenge for many families of children with autism, irrespective of their ethnic and cultural backgrounds. Kinnear et al's (2016) study in North America found that stigma and their child's autism-related behaviours played the largest roles in making parents lives challenging.…”
Section: Discussionsupporting
confidence: 91%
“…Our research supports the findings of other recent studies in Australia (Broady, Stoyles, and Morse 2015), Nepal (Heys et al 2016), Pakistan and India (Minhas et al 2015), China (Lu et al 2015), the USA and Canada (Kinnear et al 2016) that suggest stigma continues to be a significant challenge for many families of children with autism, irrespective of their ethnic and cultural backgrounds. Kinnear et al's (2016) study in North America found that stigma and their child's autism-related behaviours played the largest roles in making parents lives challenging.…”
Section: Discussionsupporting
confidence: 91%
“…The causes of autism are complex and multi-factorial (Lai et al, 2013); most cases of autism are idiopathic and this uncertainty may add to the plethora of perceived causes reported by parents of children with ASD. Examples of biological or medical explanations attributed to ASD are hereditary factors (Gona et al, 2015;Heys et al, 2017), infectious disease (Gona et al, 2015;, an accident (Al-Dababneh, Al-Zboon, & Baibers, 2016;Minhas et al, 2015;Shaked & Bilu, 2006;Tilahun et al, 2016), complications during pregnancy or birth (Al-Dababneh et al, 2016;Gona et al, 2015;Heys et al, 2017;Shaked & Bilu, 2006;Shyu, Tsai, & Tsai, 2010;Tilahun et al, 2016) or malnutrition (Gona et al, 2015;Heys et al, 2017). In the USA the most common perceived causes reported by parents are genetics/heritability and environmental risk factors, including heavy metals, food, pesticides, pollution and other exposures (Chaidez et al, 2018;Zuckerman, Lindly, & Sinche, 2016).…”
Section: Explanatory Models Of Recognised Atypical Behaviourmentioning
confidence: 99%
“…Families of children with ASD experience tremendous strain Minhas et al, 2015) and significant emotional distress, both at personal and social spheres while receiving the diagnosis of ASD.…”
Section: Prevailing Challenges In Resource-limited Settingsmentioning
confidence: 99%
“…On one hand, there is focus on addressing the lack of existing interventional modules by adapting established modules from HIC and attempting task-shifting to suit the resource needs in LAMIC (Hastings et al, 2012;Rahman et al, 2015;Wallace et al, 2012).…”
Section: Challenges In Conducting Interventional Researchmentioning
confidence: 99%